Bone tissue engineering: Production of tntz alloy by powder metallurgy - Pereira, Raíssa Monteiro; Koga-Ito, Cristiane Yumi [UNESP]; Rovetta, Sabrina Moura [UNESP]; Oliveira, Maria Alcionéia de Carvalho [UNESP]; Sampaio, Aline da Graça [UNESP]; Lima, Gabriela de Morais Gouvêia [UNESP]; Henriques, Vinicius André Rodrigues (AMG Transcend Association, 2022)
The demand for metallic biomaterials has increased proportionally to the number of elderly population and people who have bone disorders related to diseases, accidents, or premature wear. Because of this, the studies related to the development of metal alloys for applications in biomaterials have increased and Ti-29Nb-13Ta-4.6Zr (TNTZ) alloy received a great highlight. TNTZ alloy was obtained by powder metallurgy technique in order to study the microstructural development and investigate the interactions with in vivo environment. To perform this work, elementary powders were mixed in alloy stoichiometry, uniaxial and isostatically cold compacted and sintered in high vacuum (10-5 Torr) at temperatures from 800 °C up to 1600 °C. X-ray diffractometry showed a tendency for b phase stabilization at higher temperatures. The density and microhardness tests showed increasing results as the temperature increased, showing values of 5.7 g/cm³ and 352 HV. The mechanical tests presented modulus of elasticity around 40 GPa, maximum compressive strength of 1018 MPa and flexural strength of 1297 MPa. The biological tests of Ti-29Nb-13Ta-4.6Zr samples sintered at 1600 °C demonstrated antimicrobial activity against Candida albicans and Pseudomonas aeruginosa, reducing 36 and 60 % and high in vivo biocompatibility, which supports their use in implants.
Keywords: Biocompatibility; Biomaterials; Microstructural development; Powder metallurgy; Titanium alloys; TNTZ